2021
DOI: 10.1371/journal.pone.0254074
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and mental well-being of nurses in a tertiary facility in Kenya

Abstract: Background The 2019 coronavirus disease (COVID-19) epidemic is a global health emergency which has been shown to pose a great challenge to mental health, well-being and resilience of healthcare workers, especially nurses. Little is known on the impact of COVID-19 among nurses in sub-Saharan Africa. Methods A cross sectional study was carried out between August and November 2020 among nurses recruited from the Aga Khan University Hospital, Nairobi. The survey questionnaire consisted of six components- demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 31 publications
3
24
0
5
Order By: Relevance
“…Other studies conducted among HCWs in Africa during the COVID-19 pandemic reported prevalence of anxiety including mild, moderate and severe ranging from 25.5% to 90.5%. [ [10] , [11] , [12] , [13] , 17 , [23] , [24] , [25] , [26] ] The prevalence of depressive symptoms ranged between 32.1%–94.0%. [ [10] , [11] , [12] , [13] , 17 , [23] , [24] , [25] , [26] ] Most of these studies used the Generalized Anxiety Disorder 7 (GAD-7) [ 11 , 12 , 15 , 16 , 23 , 24 , [26] , [27] , [28] ] and Patient Health Questionnaire 9 (PHQ-9) [ 12 , 15 , 23 , 24 , 26 , 28 ] to determine anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies conducted among HCWs in Africa during the COVID-19 pandemic reported prevalence of anxiety including mild, moderate and severe ranging from 25.5% to 90.5%. [ [10] , [11] , [12] , [13] , 17 , [23] , [24] , [25] , [26] ] The prevalence of depressive symptoms ranged between 32.1%–94.0%. [ [10] , [11] , [12] , [13] , 17 , [23] , [24] , [25] , [26] ] Most of these studies used the Generalized Anxiety Disorder 7 (GAD-7) [ 11 , 12 , 15 , 16 , 23 , 24 , [26] , [27] , [28] ] and Patient Health Questionnaire 9 (PHQ-9) [ 12 , 15 , 23 , 24 , 26 , 28 ] to determine anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…[ [10] , [11] , [12] , [13] , 17 , [23] , [24] , [25] , [26] ] The prevalence of depressive symptoms ranged between 32.1%–94.0%. [ [10] , [11] , [12] , [13] , 17 , [23] , [24] , [25] , [26] ] Most of these studies used the Generalized Anxiety Disorder 7 (GAD-7) [ 11 , 12 , 15 , 16 , 23 , 24 , [26] , [27] , [28] ] and Patient Health Questionnaire 9 (PHQ-9) [ 12 , 15 , 23 , 24 , 26 , 28 ] to determine anxiety and depression. Other data collection tools included the 10-item Cohen Perceived Stress Scale [ 10 , 26 , 27 , 29 ], 14-item Shirom-Melamed Burnout measure [ 10 ], 7-item Insomnia Severity Index [ 12 , 26 , 28 , 30 ], 22-item Impact of Event Scale-Revised [ 12 , 28 ], 16-item Stanford Professional Fulfilment Index [ 12 , 28 ], Hospital Anxiety Depression Score [ 13 ], Coronavirus Anxiety Scale [ 17 ] and Primary Care PTSD Screen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurses are becoming health workers who are facing more psychological problems due to the COVID-19 outbreak (SK Ali, Shah, & Talib, 2021). It was also shown that nurses are at higher risk of contracting COVID-19 because they are in closer and longer contact with patients.…”
Section: Introductionmentioning
confidence: 99%